Chemical reaction engineering / Octave Levenspiel - Levenspiel, Octave
Emphasising qualitative arguments, simple design methods, graphical procedures and the capabilities of major reactor types, this reference aims to help students answer questions effectively, and develop an intuitive sense for good design.